Binding of SL3-3 enhancer factor 1 transcriptional activators to viral and chromosomal enhancer sequences. - Thornell, A (1991)
Interactions between SL3-3 enhancer factor 1 (SEF1) proteins and the enhancer of the murine leukemia virus SL3-3 were analyzed. SEF1 proteins were found to interact with two different DNA sequences within the DNA repeat region of the enhancer; these two motifs cooperated in enhancing initiation of transcription in T lymphocytes. Using an electrophoretic mobility shift assay, we identified nucleotides that are important for the SEF1 binding, and we deduced a sequence, 5'-TTTGCGGTTA/T-3' with highly improved binding of SEF1 proteins. We show that many different SEF1 binding sequences exist in the transcription control regions of different viral and cellular genes. The results indicate a general role of SEF1 proteins in T-cell gene expression.